Catalytic wet oxidation of ethanol in an integral trickle-bed reactor operated with liquid flow modulation - Fraguio, Maria Sol (2004)
The effect of liquid flow modulation on the performance of an integral trickle-bed reactor used for carrying out the catalytic wet oxidation of ethanol is analyzed. Particular emphasis is devoted to examine whether the induced periodic variations in conversion are affected by prolonged operation. A Pt/γ-Al2O3 catalyst (1% w/w, mean particle diameter dp = 0.003 m) is employed for the experiments. Liquid flow is open/closed periodically by means of a programmable logic controller with given splits and at different total cycle period. The reactor operates isothermally at 70oC during the whole cycles. The time dependence of the outlet ethanol concentration in the integral TBR is examined. In addition, the average conversion obtained with periodic operation is compared to that of the steady state at different cycle periods. It is found that the history of the operation mode has influence on the attained conversion, pointing to the existence of hysteresis affecting the particle wetting.